KONSEP PENGEMBANGAN EKOWISATA HUTAN MANGROVE DESA MOJO, KECAMATAN ULUJAMI, KABUPATEN PEMALANG - Selma Mutia; Mardwi Rahdriawan (Teknik PWK (Perencanaan Wilayah Kota), 2014)
Ecotourism is one of the special forms of the tourism activities. Ecotourism is positioned as opposed to the conventional tourism. Unlike the conventional tourism, ecotourism is a responsible tour with environmental conservation and improve the local community welfare. Citizen put down as primary factor owning importance participate directly in decision making to increase citizen prosperity through conservation effort and also natural resources exploiting. One of the activity of is mangrove forest ecotourism that can be found in Mojo, a village that  still classified on coastal region and has a lot of potential. Mangrove forest ecotourism was formed by local goverment and Japans NGO (OISCA) assisted by ‘Pelita Bahari’. Mangrove forest in Mojo covering approximately 16 hectares and has many attractions such as bird watching, mangrove tree plantation, boating, fishing, and tracking. But this potential attractions was  faced by the less optimalization of mangrove forest ecotourism activities that can be seen from the use of excessive natural resources, planting location on the edge of the estuary causes the dependence on transportation facilities, and local people who have not been able to see the economic potential that can be provided by the mangrove forest ecotourism  activities. Of the key issues above, the purpose of this study is to formulate a development concept of mangrove forest ecotourism in Mojo, related to environmental conservation and improvement of the local community welfare. Research method that used is qualitative method. Technique of data collecting that done is primary data collecting technique through field observation, interview and also spreading of quesioner. Technique of secondary data collecting through to look for data in institution, mass media article, internet and also from research which have been done previously. In reaching the aim of this research, analysis that done is identification of community efforts related to environment conservation and improvement of local welfare, lesson learned from best practice MIC Bali, and then formulated a development concept with making a zoning map. Results of this research is increasing the quality of mangrove forest ecotourism which is responsible in a way to conserve the environment and improve the welfare of local communities that can be used as a lesson learned for other villages that have similar characteristics as Mojo tourism development.